“When Life Becomes Art” -- on Hemans's “Image in Lava” - Lundeen, Kathleen (Romanticism on the Net)

(untitled) (Université de Montréal, 2003)
AbstractFelicia Hemans’s poetry is guided by an aesthetic of acute interestedness, but unlike most sentimental writers, Hemans treats feeling as something with epistemological value. This creates an interesting challenge in “The Image in Lava” since in the poem Hemans takes her sentimental stroll on the seemingly solid ground of natural science. In her rhetorical rendering of the ashen form of a mother and child, which was found during the excavations at Pompeii, Hemans suggests that the mother’s profound feelings yielded a highly romantic phenomenon: artless art. When Hemans rhapsodizes on the indestructible form of mother and child, whose love transcends mundane occurrences like death, her idealizing tendencies reveal an uncanny wisdom. The strange fact is that the forms of the mother and child have defied death. Hemans’s musing suggests an unorthodox theology: the immortal part of the mother and her child is not an interior soul that escaped the body at the moment of decease, but an exterior form that lingers amidst the ashes. By employing the conventions of sentimental literature in her response to a truly startling phenomenon—a human object—she aims to authenticate feelings that have been caricatured as clichés. Sentimental discourse thereby becomes a tool for sounding the depths of feelings and discovering the parameters of humanness.